Constitutional Compliance Atas Putusan Pengujian Undang-Undang di Mahkamah Konstitusi oleh Adressat Putusan - Sulistyowati, Tri; Nasef, Muhammad Imam; Rido, Ali (Constitutional Court of the Republic of Indonesia, Indonesia, 2020)
Theoretically and conceptually the final decision means that the Constitutional Court’s decision is the first resort as well as the last resort for justice seekers. If it is related in the context of upholding the supremacy of the constitution, it certainly does not only stop at the cancellation of a norm of law that is contrary to the constitution, but rather how the decision on annulment is then obeyed and implemented. That is because the nature of the final MK decision. However, in the recent constitutional issues, compliance by state institutions in implementing the Constitutional Court’s decision becomes a problem because there are indications of non-compliance to follow up on the final and binding Constitutional Court’s decision. Based on this, the formulation of the problem to be answered in this study is how the level of compliance with the implementation of the judicial review decision in the Constitutional Court for the period 2013-2018. The research is a juridical normative research, with the main data source, namely secondary data, data analysis using analysis Qualitative and approach methods use the statute approach and conceptual approach. The results of this study indicate that there are three categories of levels of compliance with the implementation of the 2013-2018 PUU MK ruling, namely: full compliance; partially obeyed and not obeyed. The results of the study of the authors show that the majority of MK PUU decisions were complied with totaling 59 decisions or 54.12%. However, there are also some decisions that are not obeyed in whole or in other words only partially complied with as many as 6 decisions or equal to 5.50%. Whereas the decisions that were not complied with amounted to 24 decisions or 22.01%. The remaining 20 decisions, or 18.34%, have yet to be identified in terms of compliance because of two things, namely: 1) the constitutionality period given by the Constitutional Court in its decision has not been exceeded, meaning that the legislators still have time / opportunity to follow up; 2) there has been no follow-up at all from the adressat of the decision both normatively and praxis. Thus it can be concluded that the level of compliance with PUU MK decisions for the period 2013 - 2018 is still higher than the level of non-compliance with a ratio of 54.12% compared to 22.01%.